Eco‐environmental benefits analysis of EcoPartnerships program of production technology of calcium carbonate from lime mud produced by alkaline papermaking. Issue 5 (8th June 2021) - Geng, Chao; Ma, Tao; Liu, Jianguo
Abstract: Lime mud (LM) is a kind of industrial solid waste produced in alkali recovery in papermaking industry. LM is a global environmental challenge that both China and the United States are facing. With the support of the EcoPartnership Program under the 10‐year Sino‐US Energy and Environment Cooperation Framework, China Sun Paper Joint Stock Co., Ltd. has successfully formed a partnership with America Mineral Technologies Inc. (MTI). MTI has applied the production technology of calcium carbonate from LM produced by alkaline papermaking (PTCC) to the Sun Paper Company. Compared with the traditional treatment technology of LM in Sun Paper Company, the reduction efficiency of the PTCC technology can reach 97.99%. The waste residue is relatively more stable and poses less threat to the environment than traditional technology. The energy consumption is low, and 4.15 kgce can be saved by treating per ton of LM. It does not release carbon dioxide to the environment, but consumes 0.485 tons of carbon dioxide per ton of LM on the contrary. Because the calcium carbonate produced can be used as a product, RMB 531 yuan can be saved in the treatment of each ton of LM. The PTCC process is conducive to the coordinated development of economic, environmental, and social benefits, and realizes the sustainable development of the paper industry.